Primary Diffuse B-Cell Thyroid Lymphoma: Case Report and Literature Review - Alyami, Hassan (Case Rep Oncol, 2018)
BACKGROUND: Primary thyroid lymphoma (PTL) is a rare disease, accounting for 5% of all thyroid malignancies. Diffuse B-cell lymphoma (DBCL) is the most common type of PTL. The diagnosis of PTL depends on biopsy results, and its management depends on the histological type. CASE PRESENTATION: A 66-year-old female complained of a huge neck mass on the right side that had started growing 3 months previously and was associated with compressive and B symptoms. She had undergone left hemithyroidectomy 20 years previously. On examination, a huge neck mass measuring 10 × 6 cm was detected on the right side that had shifted the trachea to the contralateral side. CT scanning revealed a huge soft tissue mass in the neck with compressive signs. Fine-needle aspiration (FNA) showed variably sized lymphocytes and large epithelial cells with occasional atypical cells. Tissue biopsy revealed DBCL, which is suggestive of PTL. DISCUSSION: PTL affects only the thyroid gland and the regional lymph nodes. Most PTL originate from B cells, especially DBCL, which accounts for 50–80% of all PTL. FNA may have limited capability to differentiate between anaplastic carcinoma of the thyroid and thyroid lymphoma. If FNA fails to determine PTL tissue, it should be determined using biopsy. A multidisciplinary approach is the best management technique for PTL. Radiotherapy, surgery, or both can be used for local control, while chemotherapy can be used for disseminated or hidden disease. CONCLUSION: Tissue biopsy is needed to exclude other differential diagnoses, whereas a multidisciplinary approach is needed to manage PTL.